KS05.5.A Alterations in white matter fiber density associated with structural MRI and metabolic PET lesions following multimodal therapy in glioma patients. (5th September 2022) - Friedrich, M; Farrher, E; Caspers, S; Lohmann, P; Stoffels, G; Filss, C; Weiss Lucas, C; Ruge, M I; Langen, K J; Shah, N J; Fink, G R; Galldiks, N; et al.
Abstract: Background: In glioma patients, multimodal therapy and recurrent tumor result in local brain tissue changes, characterized by pathologic findings in structural MRI and metabolic PET images. Little is known about these different lesion types' impact on the local white matter fiber architecture and clinical outcome. Patients and Methods: This study included data from 121 pretreated patients (median age, 52 years; ECOG, 01) with histomolecularly characterized glioma (WHO grade IV glioblastoma, n=81; WHO grade III anaplastic astrocytoma, n=28; WHO grade III anaplastic oligodendroglioma, n=12), who had a resection, radiotherapy, alkylating chemotherapy, or combinations thereof. After a median time of 14 months (range, 1-214 months), post-therapeutic structural and metabolic findings were evaluated using anatomical MRI and O-(2-[ 18 F]fluoroethyl)-L-tyrosine (FET) PET acquired on a 3T hybrid PET/MR scanner. Local fiber density was estimated from tractography based on highangular resolution diffusion-weighted imaging. A cohort of 121 healthy subjects selected from the 1000BRAINS study and matched for age, gender and education served as a control group. Results: The median volume of resection cavities, contrast-enhancing regions, regions with pathologically increased FET uptake, and T2/FLAIR hyperintense regions amounted to 20.9, 7.9, 30.3, and 53.4 mL, respectively. Compared to the control group, the average local fiber density in these regions was significantly reduced (p<0.001). Resection cavities showed the highest reduction, followed by contrast-enhancing lesions and metabolically active tumors on FET PET (relative fiber density reduction, -87%, -65%, -55%, respectively). The local fiber density was inversely related (p=0.005) to the FET uptake in recurrent tumors. T2/FLAIR hyperintense lesions, either assigned to peritumoral edema in recurrent glioma or radiation-induced gliosis, had a comparable impact on reducing fiber density (48% and 41%, respectively). The total fiber loss (average fiber loss multiplied by lesion volume) associated with contrast-enhancing lesions (p=0.006) and T2/FLAIR hyperintense lesions (p=0.013) had a significant impact on the general performance status of the patients (ECOG score). Conclusions: Our results suggest that apart from resection cavities, reduction in local fiber density is greatest in contrast-enhancing recurrent tumors, but total fiber loss induced by edema or gliosis has an equal detrimental effect on the patients' performance due to the larger volume affected. Funding: Funded by the 1000BRAINS study (INM, Research Centre Juelich, Germany), Horizon 2020 (Grant No. 945539 (HBP SGA3; SC)), and Heinz Nixdorf Foundation.